Relationship between minimally and ultra-processed food intake during pregnancy with obesity and gestational diabetes mellitus - Daniela Saes Sartorelli; Lívia Castro Crivellenti; Daniela Cristina Candelas Zuccolotto; Laércio Joel Franco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
This study aimed to investigate the relationship between food intake (considering the nature, extent, and purpose of food processing) during pregnancy and overweight, obesity, and gestational diabetes mellitus conditions. This is a cross-sectional study conducted among 785 adult women in singleton pregnancies (between 24th and 39th weeks of gestation) in Brazil. Usual food intake was estimated by the Multiple Source Method, using two 24-hour dietary recalls. The food groups of interest in this study were the unprocessed or minimally processed foods and ultra-processed foods. The World Health Organization criteria for the diagnosis of gestational diabetes mellitus and the Atalah criteria for excess weight were used. Adjusted multinomial logistic regression models were used to assess the relationship between energy contribution (%E) from foods with overweight and obesity conditions and, adjusted logistic regression models for gestational diabetes mellitus. In total, 32.1% participants were overweight, 24.6% were obese, and 17.7% of women were diagnosed with gestational diabetes mellitus . After adjustments, an inverse association between the highest tertile of %E from the intake of unprocessed or minimally processed foods and obesity was found [0.49 (0.30-0.79)]. Moreover, a positive association between the highest tertile of %E from ultra-processed food intake [3.06 (1.27-3.37)] and obesity was observed. No association between food intake (considering the nature, extent, and purpose of food processing) during pregnancy and overweight or gestational diabetes mellitus was found. The findings suggest a role of food processing in obesity but not in gestational diabetes mellitus. Further research is warranted to provide robust evidence on the relationship between the role of processed foods in obesity and gestational diabetes mellitus.